Pengembangan Model Pembelajaran Teams Games Tournament (TGT) Berbantuan Media Kartu Edukasi Belajar Pada Materi Membaca Permulaan Siswa Fase A SDN 51 Sumarambu - Rahmawati Rahmawati; Muhammad Guntur; Mirnawati Mirnawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to develop a Teams Games Tournament (TGT) learning model assisted by educational card media for beginning reading instruction for Phase A students at SDN 51 Sumarambu. The study is motivated by students’ low early reading abilities and the continued use of conventional teaching models and media, which have not optimally encouraged student activeness and learning motivation. The research employed a Research and Development (R&D) method using the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages. The results indicate that the TGT learning model assisted by educational card media is highly valid based on evaluations by subject matter, media, and language experts, and highly practical according to teacher and student responses. The implementation of this learning model was able to enhance students’ activeness, motivation, and abilities in recognizing letters, reading syllables, words, and simple sentences in accordance with the Phase A learning outcomes. Therefore, it can be concluded that the TGT learning model assisted by educational card media is effective and feasible to be used as an alternative approach for beginning reading instruction in elementary schools or Islamic elementary schools (madrasah ibtidaiyah)..